Impact Analysis Achievement Guidance in Instilling Critical Thinking and Creative Character in Elementary School Students - Faiz Wimar Fauzandy; Arief Cahyo Utomo (Lembaran Ilmu Kependidikan, 2026)
Character education, especially critical and creative thinking, is very important to develop from an early age, given the low critical thinking skills of Indonesian students based on the results of the PISA survey. This study aims to describe the impact of achievement guidance (Bimpres) in instilling critical thinking skills and creative character in students at SD Muhammadiyah 16 Karangasem. The type of research used is simple descriptive qualitative, with research subjects including 25 students and 1 achievement guidance teacher. Data collection techniques were carried out through observation, interviews, and documentation, with data validity tested using source and technique triangulation. The data analysis techniques used included data reduction (summarizing and selecting key points), data presentation (display), and drawing conclusions or verification, which were carried out continuously in the field. The results of the research and discussion show that the Bimpres activities at SD Muhammadiyah 16 Karangasem were successful in instilling critical thinking and creative character in students. The conclusion of this study is that the Bimpres program is effective as a means of strengthening intellectual character, despite facing obstacles in the form of differences in student learning speeds and time constraints. For future development, schools need to implement more effective learning planning, provide continuous motivation, intensively strengthen character, and provide facilities adequate support to maximize students' potential achievements.